2018
DOI: 10.3892/mmr.2018.9573
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑93‑5p promotes the progression of human retinoblastoma by regulating the PTEN/PI3K/AKT signaling pathway

Abstract: Numerous repor ts have indicated that microRNA-93-5p (miR-93-5p) is involved in the development and progression of human cancer, including non-small cell lung, gastric and breast cancer; however, the role of miR-93-5p in retinoblastoma (RB) remains unknown. In the present study, it was reported that miR-93-5p expression levels were significantly upregulated in RB tissues compared with in normal tissues by reverse transcription-quantitative polymerase chain reaction. Furthermore, it was demonstrated via cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Furthermore, in the RB development, PTEN showed an inhibitory effect and it served as the target of multiple miRNAs. For instance, it was the directly target of miR-93, and miR-198 in promoting human RB progression, and the decreased PTEN expression was also found, which was consists with our findings ( 34 , 35 ). In the present study, it was shown that miR-494 targeted PTEN in regulating RB cell progression, and PTEN overexpression can reverse the effect of miR-494 upregulation in RB cells.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in the RB development, PTEN showed an inhibitory effect and it served as the target of multiple miRNAs. For instance, it was the directly target of miR-93, and miR-198 in promoting human RB progression, and the decreased PTEN expression was also found, which was consists with our findings ( 34 , 35 ). In the present study, it was shown that miR-494 targeted PTEN in regulating RB cell progression, and PTEN overexpression can reverse the effect of miR-494 upregulation in RB cells.…”
Section: Discussionsupporting
confidence: 91%
“…In the field of RB research, a variety of different miRNAs have been revealed to be aberrantly expressed, and their anomalous expression plays important roles in the regulation of multiple cancer-related processes, including cell survival, proliferation, apoptosis, metastasis, angiogenesis and epithelial-mesenchymal transition (10). For instance, miR-98 (11), miR-186 (12) and miR-665 (13) are weakly expressed in RB and restrain tumor progression; on the contrary, miR-93 (14), miR-106b (15) and miR-198 are overexpressed in RB and promote tumor aggressiveness. miR-936 has been reported to exert important effects on the progression of non-small cell lung cancer (16) and glioma (17).…”
Section: Introductionmentioning
confidence: 99%
“…Of note is the relatively large decrease in miR-93 whose overexpression diminishes PTEN activity and promotes carcinogenesis through dysregulation of the PI3K/AKT pathway. 24 In general, our data show that reducing PLCβ1 substantially decreases the total amount of cellular miRs. Reduction of total cellular miRs with PLCβ1 down-regulation is in line with the large increase in small RNAs seen when PLCβ1 is overexpressed in HEK293 cells.…”
Section: Live Cell Imaging Of Mir Processingmentioning
confidence: 53%